ANALYSIS OF INDIVIDUAL BIOLOGICAL CHARACTERISTICS OF AMUR CARP (CYPRINUS CARPIO HAEMATOPTERUS) REPRODUCED USING CRYOPRESERVED SPERM - N. Kolisnyk; I. Osoba; I. Hrytsyniak (Ribogospodarsʹka Nauka Ukraïni, 2014)
Purpose. To reproduce Amur carp population using cryopreserved sperm and analyze some biological and fish culture peculiarities of the reproduced fish stock.